PHYLOGENETIC RELATIONSHIPS OF MEDICALLY IMPORTANT VIPERS OF PAKISTAN INFERRED FROM CYTOCHROME B SEQUENCES - A. Feroze; S.A. Malik; W. C. Kilpatrick (Journal of Animal and Plant Sciences, 2010)
The present study principally comprises the phylogenetic comparison of the three medically important vipers (Echis carinatus sochureki, Daboia russelii russelii and Eristicophis macmahoni) based on their molecular studies. In Pakistan, No comprehensive phylogenetic studies have so far been undertaken to collect molecular information by deciphering the cytochrome b gene (complete or partial) for the three species of interest. Keeping in mind the significance and nuisance of these deadly vipers of Pakistan, a molecular phylogeny was elaborated by successfully translating the cytochrome b gene sequence data for the three taxa of interest. Snakes for the said studies were collected through extensive field surveys conducted in Central Punjab and Chagai Desert of Pakistan from 2004 to 2006. The genetic data obtained werefurther elucidated statistically through maximum parsimony and bootstrap analysis for knowing the probable relationships among the species of interest. A comprehensive resolution of their phylogeny should be brought about for medical reasons as these lethal vipers are significant sources of snakebite accidents in many urban and rural areas of Pakistan
Keywords: Cytochrome b gene; Morphological difference; Mitochondrial DNA; Phylogeny; Vipers